2013
DOI: 10.1002/cbdv.201300086
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of Secondary Amino Acids: Replacement of Pipecolic Acid by N‐Methyl‐L‐alanine in Efrapeptin C

Abstract: The efrapeptins, a family of naturally occurring peptides with inhibitory activities against ATPases, contain several α,α-disubstituted α-amino acids such as α-aminoisobutyric acid (Aib) or isovaline (Iva) besides pipecolic acid (Pip), β-Ala, Leu, Gly, and a C-terminal heterocyclic residue. Secondary α-amino acids such as proline are known to stabilize discrete conformations in peptides. A similar influence is ascribed to N-alkyl α-amino acids. We synthesized two efrapeptin C analogs with replacement of Pip by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Accordingly, the substitution of an N -terminal glycine residue for sarcosine in an angiotensin II analog enhanced in vivo activity as a potential result of longer half-life against proteolytic degradation 6 . Similar to l -proline, N -methylated amino acids are known to stabilize discrete conformations of peptides as shown for the exchange of l -pipecolic acid by N -methyl- l -alanine in the ATPase inhibitor efrapeptin C 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the substitution of an N -terminal glycine residue for sarcosine in an angiotensin II analog enhanced in vivo activity as a potential result of longer half-life against proteolytic degradation 6 . Similar to l -proline, N -methylated amino acids are known to stabilize discrete conformations of peptides as shown for the exchange of l -pipecolic acid by N -methyl- l -alanine in the ATPase inhibitor efrapeptin C 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of proteinogenic amino acids in a peptide with an N -methylated derivative mimics the native peptide, yet, often leads to increased stability against proteases and better membrane permeability (Chatterjee et al, 2013; Di Gioia et al, 2016). Further, N -methylated amino acids are known to stabilize—similar to l -proline—discrete conformations as shown for the ATPase inhibitor efrapeptin C (Dutt Konar et al, 2013). Natural peptides containing N -methylated amino acids such as the potential anti-cancer drugs enniatins, which disrupt membrane potential by forming stacked sandwich complexes with cations in the cell membrane (Kamyar et al, 2004), and bouvardin, which blocks protein synthesis by interacting with eukaryotic 80S ribosomes (Zalacaín et al, 1982), serve as a model for synthetic peptides (peptidomimetics).…”
Section: Introductionmentioning
confidence: 98%
“…They also demonstrated that peptides with multiple N-methylated amide bonds were capable of inhibiting protein aggregation caused by intermolecular β-sheet aggregation. 13 Sewald et al have elucidated that methylated analogues of peptaibiotic efrapeptin C exhibit inhibition properties similar to that of native efrapeptin C. 14 Although significant reports are documented in the literature employing N-methylated amino acids, the design of β-turn mimetics in acyclic peptidyl systems remains in a rudimentary stage. In this report our effort lies to modulate this class of biologically important amino acid in β-turn design in short acyclic peptides.…”
Section: Introductionmentioning
confidence: 99%